NOURISHING PREFERENCES OF THE GREATER WAX MOTH WORMS (Galleria mellonella L .) WHEN THE FEEDIN - Mahdi Mohammed Salih Saeed (Mesopotamia Journal of Agriculture)
Results of studying nourishment preference of the greater wax moth worms on wax combs that vary in their pollen, honey, and metabolic wastes of bees in addition to the appearance ( dark and white ) combs and elasticity of wax base showed that the consumption of these substances varied. The study of modified multiple range Duncan's test at p=0.05 showed that the optimum nourishment,optimum time for transformation from larvae to mature insect , and largest number of eggs laid by females were of the dark colored combs that contain pollen and honey which reached (12.84gm/treatment, 32.57 days , 2039.0 eggs) respectively , and the lowest nourishment was for combs with non elastic basic wax averaging ( 5.84 grams / treatment , 47.43 days , and 56.0 eggs ) respectively , The statistical analysis of the simple correlation coefficient (r) has also revealed that theresults were significant between nourishment and both the number of eggs laid and time of transformation from larvae to mature insect throughout the study period at p= 0.01 while the correlation between the number of eggs laid and time of transformation from larvae to mature insect was less significant at p= 0.05.